2017
DOI: 10.1159/000481978
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pretreatment with Quercetin Against Lipopolysaccharide-Induced Apoptosis and the Inhibition of Osteoblast Differentiation via the MAPK and Wnt/β-Catenin Pathways in MC3T3-E1 Cells

Abstract: Background/Aims: Quercetin, a flavonoid found in onions and other vegetables, has potential inhibitory effects on bone resorption in vivo and in vitro. In our previous study, we found that quercetin treatment reversed lipopolysaccharide (LPS)-induced inhibition of osteoblast differentiation through the mitogen-activated protein kinase (MAPK) pathway in MC3T3-E1 cells. In this study, we investigated the underlying mechanisms of pretreatment with quercetin on apoptosis and the inhibition of osteoblast differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 45 publications
(45 reference statements)
1
50
0
Order By: Relevance
“…The ALOX, BCL-2, CYP 2C9, PLA2G(s) and PI3K(s) families, PLD2 and PTEN were determined as quercetin and kaempferol targets on diabetic dyslipidemia (Guo et al, 2017). PTPN1, PI3K(s) family and PLD2 were determined as targets of saponins such as quadranoside IV and asiatic acid (Ramachandran and Saravanan, 2015), whilst BCL-2, PI3K(s) family, PLD2 and PTEN were determined as action targets of gallic acid and 4-hydrobenzoic acids ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ALOX, BCL-2, CYP 2C9, PLA2G(s) and PI3K(s) families, PLD2 and PTEN were determined as quercetin and kaempferol targets on diabetic dyslipidemia (Guo et al, 2017). PTPN1, PI3K(s) family and PLD2 were determined as targets of saponins such as quadranoside IV and asiatic acid (Ramachandran and Saravanan, 2015), whilst BCL-2, PI3K(s) family, PLD2 and PTEN were determined as action targets of gallic acid and 4-hydrobenzoic acids ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…20 While, as a key signalling member of the TGF-β super family, BMP-2 is indispensable for osteoblast proliferation and osteogenic differentiation and accounts for osteogenic effect of osteoblasts to a great extent. 20 While, as a key signalling member of the TGF-β super family, BMP-2 is indispensable for osteoblast proliferation and osteogenic differentiation and accounts for osteogenic effect of osteoblasts to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 is a master transcription factor in the early-stage of osteoblast differentiation and is closely correlated with the expression of osteoblast marker genes and related proteins in the late-stage molecular events of osteoblast differentiation, such as OSX and OCN. 20 While, as a key signalling member of the TGF-β super family, BMP-2 is indispensable for osteoblast proliferation and osteogenic differentiation and accounts for osteogenic effect of osteoblasts to a great extent. 21,22 Furthermore, the changes in the expression of Runx2, BMP-2, OSX and OCN were also investigated in MC3T3-E1 cells in response to different and so on.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, it was revealed in a previous study that pretreated-quercetin suppresses lipopolysaccharide-induced programmed cell death and osteoblast differentiation by regulating MAPK and Wnt/β-catenin signal transduction in mouse osteoblasts. 23 Moreover, quercetin induces the death of human endometrial cells through mitochondria membrane permeabilization, lipid peroxidation, MAPK and PI3K/AKT signal inactivation, and regulation of cyclin D1. 24 In accord with previous evidence, in the present study, quercetin was reported to induce apoptosis through DNA fragmentation, changes of cell cycle, and ROS production in canine osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%